SAP Landscape Management 3.0 and IBM Power Systems servers - Haefele, Edmund; Beilmann, Arnold (IBM redpaper., 2019)
This IBM® Redpaper publication is part of a series of technical documentation to help the enablement of SAP on Linux for IBM Power Systems servers and IBM System Storage"!servers. This book describes how by using SAP Landscape Management (SAP LaMa) 3.0 software that clients gain full visibility and control over their SAP and non-SAP systems, including the underlying physical, virtual, and cloud infrastructures. With SAP LaMa, you can automate repetitive tasks to manage critical applications across complex, hybrid IT landscapes. This publication helps you to better control IT costs and increase business agility, for example, by freeing staff to focus on more strategic work rather than manual, error-prone tasks. The target audiences of this book are architects, IT specialists, and systems administrators deploying SAP LaMa 3.0 whom often spend much time and effort managing and provisioning SAP software systems and landscapes